The effect of (physical-skill) exercises using balls of different sizes on some physical abilities of basketball players under 16 years old - Khan, Asst.L. Hassan Abdulkarim Rustam; Rafiq, Prof. Dr. Haval Khurshid (Sulaimani Journal for Humanities, 2026)
The importance of the research was manifested in developing the level of the young players of Darbandikhan Sports Club in basketball through the preparation and design of special (physical-skill) exercises using basketballs of different sizes as a means of assistance in the training process that may give a positive effect on physical variables and raise the level and efficiency of the athlete’s technical skills according to the sound scientific principles and the results of this study.